An Analysis Identification of Physics Student Critical Thinking and Creative Thinking Skill in Physics Learning - Sri Handono Budi Prastowo; nuraini, Lailatul; Yushardi; Bambang Supriadi; Trapsilo Prihandono; Riska Uswatun Khasanah (JURNAL PEMBELAJARAN FISIKA, 2025)
The quality education depends on quality of learning process. So, it was needed to know how the student initial ability. This research aimed to describe the physics students critical thinking skill and creative thinking skill about physics concept. The method was descriptive research. The research respondents were physics students of 37 person at Class A, it consists of 5 male students and of 32 female students and physics student of 35 person at Class B, it consists of 5 male students and of 30 female students which have been take thermodynamics and modern physics on odd semester, academic year 2018/2019. The research data which was collected by using test, observation and documentation. The research data was analysed by using indicator percentage and descriptive. The result showed that average of critical thinking skill was 78,65. Interpretating around 6,8 Analysing around 8,17, evaluating around 8,97, Inferensi around 8,41 and explanation ability around 6,94. The average of creative thinking skill was 78,92. Creative thinking skill was fluency was 8,09, flexibility 8,4, originality 7,58 and elaboration 7,45. Therefore, an effort needed to improve physics student critical and creative thinking skill. It can be done by using some interactive model, media and teaching material in physics learning. Beside that needed alternative solution for development learning resource on learning physics in Higher Education with another local potential context.